The Influence of Service Quality and Brand Image on Middle School Student Satisfaction - Kristyono, Udik; Qomariah, Nurul; Thamrin, Muhammad (Budapest International Research and Critics University, 2024)
Education is an important thing that every individual must have. With education, people's knowledge will increase. This article is a concept about the impact of service quality and brand image on user satisfaction of educational services at State Middle Schools in Jember Regency. The population in this study were users of educational services at State Middle Schools in Jember Regency. The number of respondents was determined at 100 respondents provided that the respondents were for regional research. The analytical method used is multiple linear regression. The results of this research are expected to show that service quality and brand image can increase customer satisfaction at State Middle Schools in Jember Regency.